Embolization of uterine arteries with emergency assistance in patient leiomyoma with uterine bleeding - M M Damirov; L S Kokov; G E Belozerov; O N Oleinikova; G P Titova; E Yu Trofimova; O V Maiorova; S G Serzhantova (IP Berlin A.V., 2017)
The results of treatment of 65 patients with uterine leiomyoma (LM) of various sizes received with abundant uterine bleeding are analyzed. All patients underwent endovascular haemostasis by performing uterine artery embolization (EMA). The clinical features of the course of the disease after performing EMA at different tumor sizes were studied. The insufficiently high efficiency of EMA at combined defeat of uterus LM and adenomyosis is noted.